(untitled) (REMUNOM, 2025)
This study analyzes the "Women Supporting Education" subproject (M.A.E.), an initiative under the Creative and Opportunity School Project (ECO), developed by the State University of Rio de Janeiro (Uerj) in partnership with the State Department of Education of Rio de Janeiro (Seeduc/RJ). Based on Dermeval Saviani’s (2008) approach, which defines educational policy as a set of actions by the State to guide education, the work situates M.A.E. within the broader context of educational policies in Rio de Janeiro, particularly in the post-COVID-19 pandemic period. The M.A.E. subproject, implemented between December 2021 and December 2022, aimed to reduce school dropout rates and support students’ return to school. It involved scholarship recipients (the M.A.E.s), who worked to strengthen the connection between schools and communities, along with technical support from social workers. However, despite its importance, the initiative is critically analyzed for its limitations in addressing dropout primarily through statistical data, without considering students’ individual life paths. To deepen the analysis, the study draws on Bernard Lahire’s (2008) theoretical contributions, particularly his concept of a "psychological sociology," which integrates micro and macro social dimensions. This perspective allows for a better understanding of how individual dispositions, shaped by multiple social contexts, interact with the institutional demands of the school system. The research adopts a qualitative methodology, based on literature related to Brazilian educational policy and official documents, aiming to connect statistical outcomes of the subproject with broader theoretical insights. It also highlights that initiatives like M.A.E., implemented hastily and without community engagement, reflect a fragile and undemocratic educational policy. Thus, the study advocates for more integrated and participatory approaches in the development of public education policies.